2015
DOI: 10.1007/s00300-015-1695-y
|View full text |Cite
|
Sign up to set email alerts
|

A hidden getaway for bowhead whales in the Greenland Sea

Abstract: The critically endangered Spitsbergen stock of bowhead whale (Balaena mysticetus) seems to be increasing. However, research effort has also been increasing confounding a firm conclusion. A systematic aerial survey for walrus (Odobaenus rosmarus), applying distance sampling methodology in part of the Northeast Water Polynya (NEW), revealed a 'bycatch' of several observations of bowhead whales, which resulted in an estimated abundance of 102 (95 % CI 32-329) individuals. This is the largest abundance of bowhead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
3
20
0
1
Order By: Relevance
“…If part of the stock historically occupied an icecovered habitat, this fraction of the stock would not have been available to the hunters. Boertmann et al (2015) made similar conclusions regarding the animals surveyed in the Northeast Water Polynya in 2009; this area would not have been available for the early whalers because the polynya is surrounded by heavy pack ice. In addition, the most intense vocal behavior of bowhead whales from this stock has been recorded in heavy ice (Stafford et al 2012).…”
Section: Bowhead Whale Distribution and Abundancementioning
confidence: 62%
See 2 more Smart Citations
“…If part of the stock historically occupied an icecovered habitat, this fraction of the stock would not have been available to the hunters. Boertmann et al (2015) made similar conclusions regarding the animals surveyed in the Northeast Water Polynya in 2009; this area would not have been available for the early whalers because the polynya is surrounded by heavy pack ice. In addition, the most intense vocal behavior of bowhead whales from this stock has been recorded in heavy ice (Stafford et al 2012).…”
Section: Bowhead Whale Distribution and Abundancementioning
confidence: 62%
“…in contrast to the 15 sightings involving 27 individuals in this survey. This suggests that animals might have migrated into this area from other places over the past decade (Boertmann et al 2015), facilitated by the reduction in sea ice (see Heide-Jørgensen et al 2007) and increasing trends in some populations (Moore 2016), or alternatively, and most likely, this suggests a patchy, variable distribution of the animals in this stock. But, further studies are needed to confirm the degree of inter-and intra-annual variability in distribution.…”
Section: Bowhead Whale Distribution and Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Boertmann et al . () reported a corrected abundance estimate of 102 whales (95% CI 32–329) from an August 2009 aerial survey of the Northeast Water Polynya off the northeastern coast of Greenland.…”
Section: Methodsmentioning
confidence: 99%
“…: STATUS OF THE WORLD'S BALEEN WHALES 705 be increasing (Moore et al 2012b, IWC 2014. Boertmann et al (2015) reported a corrected abundance estimate of 102 whales (95% CI 32-329) from an August 2009 aerial survey of the Northeast Water Polynya off the northeastern coast of Greenland.…”
Section: Bowhead Whalementioning
confidence: 99%